A duplex PCR assay for sex determination of meat from cattle, buffalo, sheep and goat by amplification of the male specific SRY gene - GOKULAKRISHNAN, P; KUMAR, R R; SHARMA, B D; SHARMA, D (The Indian Journal of Animal Sciences, 2012)
Sex determination of domestic animal’s meat is of potential value in meat authentication and quality control studies. The objective of this study was to develop a simple and accurate PCR-based sex determination protocol, which can be applicable to cattle, buffalo, sheep and goat meat. Duplex PCR assay, including the SRY gene and the GAPDH house keeping gene, was optimized by using genomic DNA extracted from meat samples of known sex. It was possible to identify the sex of animals by amplifying both gender-specific (SRY) and autosomal (GAPDH) genes simultaneously in the duplex reaction, with the male yielding two bands and the female only one band. The protocol was subjected to a blind test showed 100% concordance, proving its accuracy and reliability.